Optimization of Halal Industrial Products with the Assistance of Digital Technology in the Industrial Revolution Era 4.0 - Fauzan, Ariq Putra; Athoillah, Anton; Salam, Annisa Nur (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: Digital transformation brings great influence and change in manysectors, and the industrial sector is no exception. However, the halal industry must be able to adapt totechnological developments to seek a wider market share.Purpose/Objective Study: This research aims to discuss the optimization of the halal industry in orderto maintain and be able to compete in the era of digital technology.Design/Methodology/Approach: This research aims to discuss the optimization of the halal industry tomaintain and be able to compete in the era of digital technology. This research uses a qualitativedescriptive method with literature study data collection techniques, by reading articles in journals, books,and other media as a reference source.Findings: The large number of technology users in the form of the internet can be used by businesspeople engaged in the halal industry to do marketing via the internet. Business people in the halal industrywho carry technology in it will have a greater chance of success.Paper Type: Research Article